1996
DOI: 10.1002/zaac.19966220217
|View full text |Cite
|
Sign up to set email alerts
|

Die Kristallstrukturen von Tl2AgI3 und NaAgI2 · 3 H2O

Abstract: Tl2AgI3 wurde durch Umsetzung von TlI mit AgI in wäßriger HI (25%) in einem Aufschlußautoklaven kristallin erhalten. Es kristallisiert in der rhomboedrischen Raumgruppe R3; a = 1044,3(2); c = 1993,5(3) pm; Z = 9. Die Kristallstruktur ist aus dreikernigen Anionen [Ag3I8]5− und [ITl6]5+‐Oktaedern aufgebaut. Die Anionen bestehen aus zwei AgI4‐Tetraedern, die über gemeinsame Flächen an ein AgI6‐Oktaeder gebunden sind. Die Verbindung NaAgI2 · 3 H2O wurde aus wäßriger Lösung durch Umsetzung von NaI mit AgI einkrista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…The Bi−I bond lengths found here are typical of those encountered in bismuth iodide hybrids. 44,46 In contrast, Ag rarely exhibits octahedral coordination with I, a few examples being Tl 2 AgI 3 (Ag−I: 3.126 Å) with a regular coordination 69 and Ag 4 I 2 SeO 4 (Ag−I: 2.878−3.458 Å) with a distorted coordination with O and I. 70 These Ag−I bond lengths are comparable to those found in our relaxed structure.…”
Section: ■ Results and Discussionsupporting
confidence: 82%
“…The Bi−I bond lengths found here are typical of those encountered in bismuth iodide hybrids. 44,46 In contrast, Ag rarely exhibits octahedral coordination with I, a few examples being Tl 2 AgI 3 (Ag−I: 3.126 Å) with a regular coordination 69 and Ag 4 I 2 SeO 4 (Ag−I: 2.878−3.458 Å) with a distorted coordination with O and I. 70 These Ag−I bond lengths are comparable to those found in our relaxed structure.…”
Section: ■ Results and Discussionsupporting
confidence: 82%
“…XRD confirmed that the pre-synthesized binary and ternary compounds were phase-pure, and that the unit cell parameters perfectly matched the literature data for all ternary compounds: AgTlI2, AgTl2I3, and AgTl3I5 [6][7][8].…”
Section: Discussionsupporting
confidence: 63%
“…There are three phases reported to exist in the Ag-Tl-I system, AgTl 2 I 3 , AgTlI 2 , and AgTl 3 I 5 , with the two former belonging to the AgI-TlI quasi-binary subsystem. AgTl 2 I 3 crystallizes in the trigonal system, space group R-3m, with the unit cell parameters а = 10.443 and c = 19.935Å [6], AgTlI 2 has a tetragonal crystal structure, space group I4/mcm; а = 8.34; c = 7.66Å [7], and AgTl 3 I 5 crystallizes in the hexagonal system, space group P62c, with the unit cell parameters а = 10.480; c = 13.415Å [8]. Their crystal structures are different; however, they can be described in a similar manner, emphasizing the coordination polyhedra of silver.…”
Section: Introductionmentioning
confidence: 99%
“…Within these hcp anion arrays we assume that the Zn 2+ are located in sites which are tetrahedrally co-ordinated to four I − , as is the case in the binary compound ZnI 2 [21]. The same environment is also the most likely for Ag + (as in both wurtzite structured β-AgI [2] and zincblende structured γ -AgI [1]), though in a small number of ternary compounds, such as AgTl 2 I 3 [22], Ag + is found in octahedral environments. The orthorhombic unit cell found for β-Ag 2 ZnI 4 contains 16 tetrahedral and eight octahedral interstices, which must accommodate 4 × Ag + and 2 × Zn 2+ .…”
Section: Neutron Diffraction Results: Ag 2 Znimentioning
confidence: 99%